The prevalence and risk factors of sexual dysfunction in gynaecological cancer patients. - Tee, BC; Ahmad Rasidi MS,; Mohd Rushdan MN,; Ismail A,; Sidi H, (Penerbit UKM, 2014)
Sexual dysfunction is highly prevalent in gynaecological cancer patients. Most of the time, sexual dysfunction in gynaecological cancer is underdiagnosed as there is overlapping of symptoms with other psychological morbidities, interplaying of multiple risks, patients’ reluctance to complain or incompetence of health care provider to assess. Determining the risk factors of sexual dysfunction in cancer patients enables us to pay more attention to those who are vulnerable and to device strategies for early detection, prevention and treatment of sexual dysfunction in them. The main aim of the study was to determine the prevalence of sexual dysfunction and its risk factors in gynaecological cancer patients in Hospital Sultanah Bahiyah, Alor Star, Malaysia. Sexual function of eighty-three gynaecological cancer patients who were married were assessed with self-rated MVFSFI (Malay version Female Sexual Function Index). Self-rated WHOQOL-BREF (World Health Organization- Quality of Life- 26) which assessed the domains of quality of life was used while MINI (Mini International Neuropsychiatry Interview) was used for diagnosis of major depressive disorder. The prevalence of sexual dysfunction among the married gynaecological cancer patients was 65% (54/83). Sexual dysfunction was significantly associated with low education level (OR 3.055, CI 1.009-9.250), shorter duration of cancer (OR 0.966, CI 0.966- 0.998), ongoing chemotherapy (OR 3.045, CI 1.149-8.067), pain perception (OR 3.230, CI 1.257-8.303), absence of sexual intercourse for more than one month (OR 1.862) and three domains of quality of life such as physical health, psychological health and social relationship (OR 0.942, CI 0.908-0.978; OR 0.955, CI 0.916-0.995; OR 0.933, CI 0.894-0.973, respectively). However, sexual dysfunction was not associated with major depressive disorder (χ2² = 1.224, p = 0.268). The prevalence of sexual dysfunction in gynaecological cancer patients was comparable to other studies of similar population. Since, the risk factors of sexual dysfunction in gynaecological cancer patients are multidimensional, the process of assessment and management need to be holistic and patient-oriented.